Model Promosi Kreatif “AISAS” pada Perguruan Tinggi Jarak Jauh di Indonesia dalam Peningkatan Rekrutmen Mahasiswa Baru - Sri Maulidia Permatasari; Melisa Arisanty; Eko Kuswanti; Yasir Riady; Selly Anastasia (Communications, 2024)
The existence of higher education in this era of technological disruption causes the practice of higher education to change fundamentally. In the past, higher education was carried out mostly face-to-face or face-to-face, now with the help of technological disruption, the educational process no longer needs to be face-to-face but online. Therefore distance education is directed to be the education of choice in the face of the Industrial revolution 4.0. The Universitas Terbuka as a pioneer of distance learning or education, which from the beginning was founded has implemented a distance learning system. The Universitas Terbuka needs to introduce and interest the public about an education system that is different from the usual one. Here the role of UPBJJ UT as part of the Universitas Terbuka becomes very important. UPBJJ-UT is required to design a promotion plan and create creative strategies in order to attract public interest so as to increase the number of students. Therefore, it is very important to explore in depth various interesting promotional strategies from various UPBJJ-UT in Indonesia. Based on the results of research using a qualitative approach, namely the interview method combined with the AISAS promotion model and the promotion mix, it was found a new promotional design that can be an example and can be applied in all agencies that implement distance education to attract and increase public interest (number of students).